(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
While extant scholarship examining the relationship between Corporate Social Responsibility (CSR) and ownership structure, no work has examined how Mandatory CSR impacts the CSR-Ownership structure nexus. Coercive pressure from law plays a crucial role in influencing how the ownership structure of companies can affect the CSR performance. Accordingly, it is crucial to understand the difference between CSR and ownership structure relationship before and after the implementation of Section-135 of the Companies Act, 2013 in the Indian context. In the present study, we draw on institutional theory to explore if the corporate sector responds to institutional pressures. Our analysis of a sample of NIFTY 100 index firms for the period 2010-2019 illustrates that the impact of ownership structure on CSR is higher in the period after the implementation of mandate. Our theoretical arguments and results emphasize the value of multiple perspectives to evaluate the impact of Mandatory CSR on the link between CSR and ownership structure.